Epigenetic Silencing of TFPI-2 in Canine Diffuse Large B-Cell Lymphoma - Ferraresso, Serena (Public Library of Science, 2014)
Epigenetic modifications are important early events during carcinogenesis. In particular, hypermethylation of CpG islands in the promoter region of tumor suppressor genes is a well-known mechanism of gene silencing that contributes to cancer development and progression. Tissue factor pathway inhibitor 2 (TFPI-2) is a tumor suppressor involved in invasiveness inhibition. Although TFPI-2 transcriptional silencing, through promoter hypermethylation, has been widely reported in several human malignancies, it has never been explored in lymphoma. In the present study TFPI-2 methylation and gene expression have been investigated in canine Diffuse Large B-cell lymphomas (cDLBCL). The methylation level of 23 CpGs located within the TFPI-2 promoter was investigated by bisulfite-specific PCR and next generation amplicon deep sequencing (GS Junior 454, Roche) in 22 cDLBCLs and 9 controls. For the same specimens, TFPI-2 gene expression was assessed by means of Real-time RT-PCR. Sequence analysis clearly demonstrated that TFPI2 is frequently hypermethylated in cDLBCL. Hypermethylation of the TFPI-2 promoter was found in 77% of DLBCLs (17 out of 22) and in one normal lymph node. Globally, dogs with DLBCL showed a mean methylation level significantly increased compared to controls (p<0.01) and analysis of hypermethylation by site identified 19 loci out of 23 (82%) with mean methylation levels from 2- to 120-fold higher in cDLBCL. Gene expression analysis confirmed a significant down-regulation of TFPI-2 (p<0.05) in DLBCLs compared with normal lymph nodes, suggesting that TFPI-2 hypermethylation negatively regulates its transcription. In addition, a significant positive correlation (p<0.01) was found between TFPI-2 methylation levels and age providing the first indication of age-associated epigenetic modifications in canine DLBCL. To conclude, our findings demonstrated that epigenetic dysregulation of TFPI-2, leading to its reduced expression, is frequently detected in canine DLBCL. In the next future, the aberrant TFPI-2 promoter hypermethylation may be considered in association with prognosis and therapy.